ISOLASI DAN ELUSIDASI STRUKTUR TRITERPENOID KULIT BATANG SURIAN Toona sinensis DAN UJI TERHADAP HAMA Crosidolomia pavonana - Adlis Santoni; Hazli Nurdin; Yunazar Manjang; Sjamsul A Achma (Jurnal Riset Kimia, 2010)
ABSTRACT Tryterpenoid compound (3-hydroxyeupha-7-ene) were isolated from hexane fraction the steam bark of Toona sinensis (Meliaceae). The structures of these compounds were established base on spectroscopic evidence, including UV, IR, 3C-NMR, 1H-NMR, HMBC, HMQC and COSY spectra and literature survey this is new compound in family Meliaceae. Insect activity of the hexane fraction (1.0%) and against Crosidolomia pavonana were tested. The activity of hexane were mortality (37.5%), antifeeding (75.5%). The activity of the 3-hydroxyeupha-7-ene showed mortality (52.0%), Lc50; 0.39847 and Lt50; 5.53931. Keywords: Toona sinensis (Meliaceae), 3-hydroxyeupha-7-ene, Crosidolomia pavonana, Antifeeding, Mortality Lc50 and Lt50